PENINGKATAN KEMAMPUAN MENULIS NASKAH DRAMA BERDASARKAN CERPEN YANG DIBACA MELALUI STRATEGI STRATA PADA PESERTA DIDIK - Salman Suratinoyo (Ideas Publishing, 2018)
This classroom action research aims to improve the ability to write drama script based on short stories that are read by using Strata strategy. The research was conducted in SMP Negeri 13 Gorontalo by taking the subject of research on the students in class IX-1 which amounted to 31 people. Data collection was done by using observation sheet of teacher activity, observation sheet of learners activity, and written test. Data analysis technique used qualitative descriptive and quantitative analysis. The results showed that the application of Strata strategy can improve the ability to write drama script based on short stories read. If the initial test results the ability of learners on average only 37.61% of 31 students. After the Strata strategy applied in cycle I, the average ability of the students has increased to 53.74%. Some deficiencies in cycle I improved in cycle II so that the average ability of learners increased to 95.67%.